Otimização dos níveis de tripolifosfato de sódio e cloreto de cálcio em marinados de carne caprina - Ferreira, Dayana do Nascimento (2013)
The nutritional advantages of goat meat are related to low fat, high digestibility, and high levels of protein, iron and unsaturated fatty acids. The marination is an alternative used to add value to the meat as it improves its acceptance, especially to increase the juiciness, flavor and tenderness. The objective was to optimize the levels of sodium tripolyphosphate (STPP) and calcium chloride (CaCl2) in marinated goat meat using as raw material, cut Monday, goat's neck, evaluating their effect on the characteristics physicochemical and sensory properties. We used a 22 full factorial design, with 4 factorial points, 3 central points (level 0) and four axial points (± α), totaling 11 experiments, whose independent variables were sodium tripolyphosphate (0 to 0.5%) and Calcium chloride (0 to 4M). The physico-chemical responses were: composition, pH, water holding capacity (WHC), water activity (Aw), color (L *, a *, b *), shear force (FC) and cooking losses (PC). Sensory responses were: color, aroma goats, salty, bitter aftertaste, tenderness, juiciness and overall evaluation, which was used scales unstructured nine inches. Analyses were conducted with 16 trained panelists using a methodology based on Quantitative Descriptive Analysis (QDA). We evaluated the profile of fatty acids, cholesterol and amino acids for characterization of the product. Responses ash, pH, shear force, tenderness, juiciness and overall assessment models generated statistically significaticos. The results of this study indicate that the levels studied, the addition of sodium tripolyphosphate favored in getting marindos goat meat with smaller values of shear strength, softness, juiciness and overall acceptance, this variable was also primarily responsible for the pH of the meat; band optimized for application in marinated goat meat obtained was 0.25 to 0.5% for improving responses studied. Calcium chloride had less effect on the response variables pH, shear force, tenderness, juiciness and overall evaluation, suggesting that the use of salt in marinated meat goats must be applied in minute concentrations, the optimal range for the use of this salt the product was 0 to 0.1 M. As the profile of amino acids and lipids, the results indicate that the product produced is a source of essential amino acids and is similar to lipid quality prime cuts of the animal; was also verified that the cholesterol found in the product produced is below the recommended maximum level , which makes the product an excellent source of nutrition.